Peningkatan Literasi Digital Marketing dan Penerapan Digital Marketing di Desa Nambangrejo Dukuh Tengah - Ramadhan, Rezha Ramadhan; Khafidhoh, Khafidhoh (Social Science Academic, 2024)
The community of Nambangrejo Village, particularly in Dukuh Tengah, faces challenges in accessing and understanding digital technology and e-commerce platforms. Limited telecommunications equipment and a lack of technological knowledge hinder their ability to shop online and manage digital transactions. Additionally, a preference for direct transactions over digital methods poses a barrier. This study aims to enhance the digital literacy of the Nambangrejo community by organizing digital marketing training. Specific objectives include understanding digital marketing strategies, mastering digital marketing tools and platforms, improving analytical skills, encouraging creativity, and ensuring adaptation to current trends. The training was conducted twice on July 27 and July 29, 2024, at Balaidesa Nambangrejo. The participants, selected through a community meeting, were local youth. The training featured an expert speaker, Imam Mustaqim, S.Pd., and was attended by the Field Supervising Lecturer (DPL) and the Village Secretary. The methodology included theoretical instruction, case studies, and practical exercises. Data collected include documentation of the training, photographs of activities, and participant feedback. Evaluation was conducted to measure the participants' improvement in understanding and skills related to digital marketing. The training successfully enhanced participants' understanding of digital marketing strategies and e-commerce platforms. Participants showed progress in analytical skills and digital marketing budget management. However, further efforts are needed to ensure sustained adaptation to technological advancements and current trends. This initiative is expected to assist the community in leveraging technology for local business development and improving access to digital markets